Analysis of Compensation Systems Based on Salary Mapping Adhered and Overlapping Methods in RL SMEs - Annisa Cahya Arindi; Febya Noor Adhani Budiman; Layalia Briliani Az-Zahra; Lia Septina; Niftira Fajriah; Lindawati Kartika (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
RL SMEs operates a business in the food & beverage sector. In providing compensation to employees, the salary mapping system of RL SMEs considers ten compensable factors. The ten compensable factors used are education, experience, communication, problem-solving analysis, customer service orientation, planning & coordination, working conditions, freedom of action, physical effort, and impact & influence. Providing compensation to RL SMEs aims to create internal justice and to improve employees performance and productivity. One indicator of the compensation system is ideal, namely when the mid to mid is smaller than the spread. Meanwhile, the compensation system for RL SMEs could be better because there is still a mid to mid value more significant than the spread value, so it is necessary to improve salaries using adhered and overlapping methods. In this study, we collected data by interviewing RL SMEs owners and distributing questionnaires to RL SMEs employees. The researchers conducted this research in Kebayoran Baru, South Jakarta. The results of this study indicate that an effective and efficient method of improving base salary for RL SMEs is the overlapping method because it results in an increase in salary for each grade that is not too far from the actual base salary and a more even distribution of salary.